(untitled) (Research, Society and Development, 2023)
Reproduction is the beginning of animal production, for its success it is necessary that breeders have superior productive quality and that they transmit the desired characteristics to their descendants. This work was carried out with the aim of describing a body growth model for a group of bullfrog breeders. 30 images were used with an initial average weight of 12.78 g. Males and females were housed in the same tank in a flooded system. All frogs were weighed to collect live weight data, totaling 19 data collections over 434 days. The Gompertz model (Pt = Pm . e .(- e . (- b .( t - t* )))) was adopted to describe the growth of frogs. Of the initial 30 images, 16 were male and 14 female. The asymptotic values of weight at maturity (Pm) for live weight for both sexes; men and women, respectively, were 656.9; 626.3 and 679.2g; the values found for b (relative growth rate) were respectively 0.0138; 0.0147 and 0.0140 g/day and the value of t that represents the day on which growth rates are maximum respectively were 173.3; 169.5 and 175.0 days. The frogs reached a commercial weight of 250 g after 176 days of rearing. Using the curves generated by breeders, it will be possible to evaluate their descendants in terms of growth and, therefore, the statistical data obtained in this research can be used as a basis for genetic selection.